Obstacle clearance performance in individuals with high body mass index. (January 2023) - Lim, Sol; Luo, Yue; Lee-Confer, Jonathan; D'Souza, Clive
Abstract: The objective of this study was to quantify performance in an obstacle clearance task among individuals with excess body weight or body mass index (BMI). Task performance was operationalized as the maximum obstacle height cleared, four duration measures of successful task completion and compensatory movements used in the process of task completion. Eighteen participants with a BMI exceeding 30 kg/m 2 completed a laboratory experiment that required stepping over seven lightweight obstacles. Obstacle heights were sequentially increased from 36 cm in 5 cm increments until participants were unsuccessful or unable to clear the obstacle up to 66 cm. Successful task completions decreased from 100% at an obstacle height of 36 cm to 66.1% at 66 cm. Higher obstacle heights were associated with significantly fewer task completions, longer leading and trailing leg stance and overall task duration, and more frequent use of compensatory movements for successful obstacle clearance. Cox PH regression was used to test the association between probability of obstacle clearance and normalized obstacle height adjusting for BMI, standing balance, and type of compensatory movement used, namely, hover and pivot motions involving the leg, and hands for bracing. The probability of successful task completion significantly decreased with increases in BMI (hazard ratio, HR = 1.14, 95% CI: 1.05–1.25), and increased with use of a leg pivot motion (HR = 0.30, 95% CI: 0.09–0.96) during task completion, after adjusting for standing balance and other types of compensatory movements. Overall, the results demonstrated that obstacle clearance performance is affected by an individual's BMI and the use of compensatory behaviors for regaining stability. The ability to recruit internal and external stabilization techniques could potentially serve as a clinical indicator of reduced fall risk and be the focus of fall prevention interventions. Implications for evaluating stability, fall risk, and identifying modifiable factors for fall prevention in the obese population are discussed. Highlights: Obstacles with heights up to 41 cm were successfully cleared by all participants with high BMI. Success rate decreased to 66.1% at the 61 cm and 66 cm obstacle height, each. Leg hover and pivot, and hand contact with the wall were frequently used compensatory movements. Higher BMI increased the hazard ratio (HR = 1.14) in the obstacle clearance task. Leg pivot movements decreased the hazard ratio (HR = 0.30) in the obstacle clearance task.